Teaching Writing of Recount Text by Using Comic Strips - Arifin, Samsul; Riyanti, Dina (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2018)
The objectives are to describe the implementation, the advantages, and the disadvantages of teaching writing of recount text by using Comic Strips for the tenth grade students of senior high school. The researcher uses qualitative research as an approach and descriptive research as type of research. The result shows that the stages of implementing Comic Strips media in the classroom are introducing the media, explaining and analyzing the recount text, redistributing the media with other topic, asking the students to read and pay attention to, writing a recount text based on the Comic Strips given, monitoring the students’ difficulties, correcting their mistakes on writing the text, writing the final draft based on the teacher’s suggestion and comment, submitting the final writing, reviewing and giving feedback to the lesson, and closing. The advantages of the implementation of the media are that, firstly, it can stimulate the students’ imagination and creativity so that they can obtain greater ideas in order to make a good composition. Second, it gives students the clue of chronological events which then it helps students to memorize and visualize better. Third, it facilitates the students to develop their own ideas and arrange words into good sentences of recount text by understanding both the story of pictures and the conversations in English illustrated in dialogue balloons. The last the students can easily find new vocabularies from the texts of conversations being conveyed by the characters in the media. Meanwhile, the disadvantages are first, there are some students who still make mistakes especially on their grammar and vocabulary. Second, the students often forget about using right capitalization and punctuation. Based on the result of the study, it is suggested to use Comic Strips to improve the students’ writing on other text types. Keywords: recount text, comic strips,